Mercury levels and tolerable weekly intakes (TWI) of tuna and tuna-like species from the Southern Indian Ocean (Indonesia): Public health perspective - TRI HANDAYANI; MOHAMAD SYAMSUL MAARIF; ETTY RIANI; NAZORI DJAZULI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Handayani T, Maarif MS, Riani E, Djazuli N. 2019. Mercury levels and tolerable weekly intakes (TWI) of tuna and tuna-like species from the Southern Indian Ocean (Indonesia): Public health perspective. Biodiversitas 20: 504-509. Tuna and tuna-like species are essential sources of protein for much of the world and provide employment in areas where fishing and processing are concentrated, as well as their value are confirmed as extremely valuable. However, their benefits may be overshadowed by the presence of mercury. The main objectives of the study were to analyze mercury content in tuna and tuna-like caught from Southern Indian Ocean related to its correlation with the weight of fish. The method used was linear regression and tolerable weekly intake (TWI) calculation. Mercury levels in yellowfin tuna (Thunnus albacares) and bigeye tuna (Thunnus obesus) indicated significant variations with the level that ranged from 0.049 to 0.654 mg/kg across individual fish weight, while for tuna-like ranged from 0.014 to 1.908 mg/kg. All mercury levels in tuna not exceeded 1.0 mg/kg, while for tuna-like 7.3% (30 kg up), 27.3% (51 kg up) and 34% (51 kg up) for oilfish (Lepidocybium flavobrunneum), marlin (Makaira indica) and swordfish (Xiphias gladius) were exceeded of 1.0 mg/kg respectively. TWI calculation indicates that people who are not in high-risk categories (most adult and adolescents) may consume about 1,000 g of tuna a week and less than for tuna-like.